Self-adaptive forward–backward splitting algorithm for the sum of two monotone operators in Banach spaces - Bello, Abdulmalik U.; Chidume, Charles E.; Alka, Maryam (Fixed point theory and algorithms for sciences and engineering, 2022)
In this work, we prove the weak convergence of a one-step self-adaptive algorithm to a solution of the sum of two monotone operators in 2-uniformly convex and uniformly smooth real Banach spaces. We give numerical examples in infinite-dimensional spaces to compare our result with some existing algorithms. Finally, our results extend and complement several existing results in the literature.